ANALISIS PERATURAN BUPATI BANTUL NOMOR 34 TAHUN 2010 TENTANG PERUBAHAN ATAS PERATURAN BUPATI NOMOR 12 TAHUN 2010 TENTANG PENATAANTOKO MODERN DI KABUPATEN BANTUL - , Fajrul Mumtaz Kurniawan, SH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study was intended to learn the analysis of Bantul Regent Decree Number 34 Year 2010 about Modification over Regent Decree Number 12 Year 2010 about Modern Store Arrangement in Bantul District viewed from business competition law and capital investment law, also to learn application prospect of Bantul Regent Decree Number 34 Year 2010 about Modification over Regent Decree Number 12 Year 2010 about Modern Store Arrangement in Bantul District. This study was empiric-juridical that is study discussing juridical aspect a legislation regulation by viewing and analyzing its implementation. This study combined normative approach and empirical approach, in where its discussion not only the regulation aspect (secondary data) but also using field observation result and respondents interview (primary data) as analizing materials. Field study was carried out by interviewing the informant and respondents. Data obtained analyzed using qualitative method. Study result showed that Bantul Regent Decree Number 34 Year 2010 about Modification over Regent Decree Number 12 Year 2010 about Modern Store Arrangement in Bantul District in line with business competition law and capital investment law. Implementation prospect of this Regent Decree can be viewed from 3 (three) aspects, namely economical aspect, socio-cultural aspect, amd polical aspect. From economical aspect that is to enhance Bantul citizensâ well being, from socio-cultural aspect that is to perpetuate politeness, mutual assistance, fellowship culture, and above all to nurture solidarity and this national unityis one the government wants to develop, accordance with potency, characteristic, and also economic issue in Bantul District, whereas from political aspect in which Bantul District government has the authority to regulate and administrate its area of authorization according to autonomy principle and assistance task in this case is issuing Regent Decree.